Sikap Petani Terhadap Program Padi IP 400 di Kabupaten Cilacap: Surur Hidayat, Siti Minarsih, Hernowo - Surur Hidayat, Siti Minarsih, Hernowo Surur Hidayat, Siti Minarsih, Hernowo (Sumber Penyuluhan Pertanian Indonesia, 2023)
The agricultural sector, especially rice commodities in Indonesia, is still the main sector in meeting national consumption needs. In order to create a balanced condition to a surplus of rice commodities, the Indonesian government strives to focus on agricultural development activities. Paddy fields as one of the natural resources have in fact undergone land conversion. Almost similar conditions occurred in Cilacap Regency. Based on BPS data (2021), past five years the harvest area in Cilacap Regency has decreased. This condition was alarming, so the government launched a new policy to support food security in Central Java Province. The policy is an optimization program for increasing the crop index or called IP 400. The purpose of the study was to examine the attitudes of farmers in the program in Cilacap Regency. The research was conducted in Cilacap Regency, Central Java Province. This research was conducted in July 2022. The research method used the survey method. The sample was 64 respondent farmers using census method. Attitude variables were analyzed using descriptive analysis with likert scale. The attitude of farmers in the program in Cilacap Regency, which is 39 percent, is positive, which means that farmers support the program. As 61 percent still don’t support the program.